2017
DOI: 10.1161/jaha.116.005381
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Complete Revascularization in Acute Coronary Syndrome: A Systematic Review and Meta‐Analysis

Abstract: BackgroundStudies have suggested that complete revascularization is superior to culprit‐only revascularization for the treatment of enzyme‐positive acute coronary syndrome. However, the optimal timing of complete revascularization remains unclear. We conducted a systematic review and meta‐analysis of randomized controlled trials comparing single‐stage complete revascularization with multistage percutaneous coronary intervention in patients with ST‐segment elevation myocardial infarction or non–ST‐segment eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
0
24
0
2
Order By: Relevance
“…Both females and males, had better outcomes in terms of mortality, MACE and overall complications when complete revascularization was performed. [21][22][23][24] In addition, 90-day follow-up data from the PROTECT II trial showed a significant decrease in major adverse 30-day survival rates Secondary outcomes such as major adverse cardiac events, dialysis requirement, bleeding within 72 hr, blood transfusion, dysrhythmia were similar in both cohorts. 25 Complete revascularization is often achieved with CABG surgery and has been shown to be associated with long-term mortality benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Both females and males, had better outcomes in terms of mortality, MACE and overall complications when complete revascularization was performed. [21][22][23][24] In addition, 90-day follow-up data from the PROTECT II trial showed a significant decrease in major adverse 30-day survival rates Secondary outcomes such as major adverse cardiac events, dialysis requirement, bleeding within 72 hr, blood transfusion, dysrhythmia were similar in both cohorts. 25 Complete revascularization is often achieved with CABG surgery and has been shown to be associated with long-term mortality benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Early percutaneous coronary intervention (PCI) can restore blood flow to ischemic myocardium, decrease infarct size, and reduce mortality and complications [1], but about 10-30% of patients exhibit no-reflow or slowreflow phenomena after PCI, which seriously affects prognosis [2]. The main cause of no-reflow or slow-reflow after PCI is coronary microembolism (CME) [3], resulting in myocardial cell necrosis and apoptosis, ventricular remodeling, malignant arrhythmia, and cardiac failure [4].…”
Section: Introductionmentioning
confidence: 99%
“…ACS including unstable angina pectoris(UA),non-ST-elevated myocardial infarction(NSTEMI)and ST-elevated myocardial infarction(-STEMI) is associated with substantial morbidity and mortality rate [1,2], and thus becomes the foucs of treatment. Coronary revascularization is an effective treatment for acute coronary syndrome [3,4] including percutancous coronary intervention (PCI), coronary artery bypass grafting (CABG) and hybrid coronary revascularization (HCR). SYNTAX score mainly conducts quantitative analysis according to the anatomical characteristics of coronary artery, such as location, length, stenosis degree, bifurcation, etc., which is a comprehensive assessment method for evaluating the severity of coronary artery lesion [5,6].…”
Section: Introductionmentioning
confidence: 99%